In Memory of William Corliss - Huyghe, Patrick (Journal of Scientific Exploration, 2011)
<!--[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif] --> William R. Corliss, regarded by many as the world’s greatest contemporary anomalist, passed away at his home in Glen Arm, Maryland, on July 8, 2011, at the age of 84. During a span of some 40 years, the physicist turned stalker of paradoxical data brought to light a mind-boggling collection of unexplained observations, embarrassing deviations, and paradigm-shattering discoveries that orthodox science had largely swept under the carpet of consensus. In recognition of these contributions, he received, in 1994, the Tim Dinsdale Award presented by the Society for Scientific Exploration.